2007
DOI: 10.1093/carcin/bgl255
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A--target of CUTL1 and potent modulator of tumor cell migration and invasion in pancreatic cancer

Abstract: Previously, we have identified the transcription factor CUTL1 as an important mediator of tumor invasion and target of tumor growth factor-beta. Using high-throughput approaches, we identified several putative downstream effectors of CUTL1, among them WNT5A, a secreted member of the Wnt multigene family. The aim of this study was to investigate the role of WNT5A as a novel target of CUTL1 in pancreatic cancer. CUTL1 and WNT5A were stably over-expressed as well as transiently and stably knocked down by RNA inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 39 publications
8
130
0
1
Order By: Relevance
“…However, since these fusion genes are limited to certain types of leukaemia, a broad spectrum diagnosis marker and the index of curative effect assessment is needed that can diagnose leukaemia at an early stage reflecting the change required in treatment. Both our research and past reports have showed that there are remarkable differences in Wnt5a expression levels not only between normal and solid tumor tissues (16)(17)(18)(19), but also between normal or non-malignant hematopoietic tissue and most blood malignancies (20)(21)(22)24,28). Loss of expression of Wnt5a may be one of the reasons that hematopoietic cells obtain malignant proliferation ability.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, since these fusion genes are limited to certain types of leukaemia, a broad spectrum diagnosis marker and the index of curative effect assessment is needed that can diagnose leukaemia at an early stage reflecting the change required in treatment. Both our research and past reports have showed that there are remarkable differences in Wnt5a expression levels not only between normal and solid tumor tissues (16)(17)(18)(19), but also between normal or non-malignant hematopoietic tissue and most blood malignancies (20)(21)(22)24,28). Loss of expression of Wnt5a may be one of the reasons that hematopoietic cells obtain malignant proliferation ability.…”
Section: Discussionsupporting
confidence: 62%
“…The ROR2 pathways: Wnt5a can bind and activate the ROR2 tyrosine kinase receptor resulting in the activation of the actin-binding protein, filamin A, and the JNK signaling pathway (11,14). This pathway also can stimulate the TAK1-NLK pathway to phosphorylate (11) and inactivate the active ß-catenin transcription complex (12,15 (16)(17)(18)(19), and Wnt5a has been reported to facilitate cell invasion in human metastatic melanoma (20). However, the function of Wnt5a is complicated as recent findings suggested that it may have an anti-oncogenic role.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical analysis on separate series of breast and pancreatic cancers confirmed that p200 CUX1 protein expression was increased in the high histological grade tumours compared with low-grade tumours 13,58 . Interestingly, CUX1 mRNA and protein expression is increased by TGFβ and is required for TGFβ-induced cell migration and invasion 13,43 .…”
Section: Interstitial Fibrosismentioning
confidence: 80%
“…Most cancer-related deaths are due to metastatic spread, highlighting the need for effective anti-metastatic therapeutics. Wnt5a has also been implicated in promoting cell migration in other tumors such as prostate (32), pancreatic (33), gastric (34), and non-small-cell lung cancers (35), suggesting that Box5 could have far wider potential use as an anti-metastatic drug. In a broader context, Wnt5a is also thought to promote chronic inflammatory diseases such as psoriasis and rheumatoid arthritis (36)(37)(38), highlighting further possible applications for Box5.…”
Section: Discussionmentioning
confidence: 99%